2020
DOI: 10.1101/2020.06.22.146282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring the collective behavior of enzymatic nanomotors in vitro and in vivo by PET-CT

Abstract: Enzyme powered nanomotors hold great potential for biomedical applications, as they show improved diffusion and navigation within biological environments using endogenous fuels. Yet, understanding their collective behavior and tracking them in vivo is paramount for their clinical translation. Here, we report on the in vitro and in vivo study of swarms of selfpropelled enzyme-nanomotors and the effect of collective behavior on the nanomotors distribution within the bladder. For that purpose, mesoporous silica n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 67 publications
(26 reference statements)
1
39
0
Order By: Relevance
“…More investigations into these fundamental aspects will be necessary to optimize the fabrication and performance of these devices, but also reduce their side effects. Future research should focus more on the fundamental interactions with biological matrices (Palagi et al, 2017; Walker et al, 2015; Z. Wu et al, 2018) and also in the interaction between several of these nanomotors, which would also offer an interesting system to study in active matter physics (Hortelao, Simó, et al, 2020; Illien et al, 2017). The effects elements like ionic species or pH on the motion efficiency still need to be further investigated, as seemingly contradictory results arise (Arqué et al, 2020; De Corato et al, 2020; Tang et al, 2020), hinting at a much more complex interaction between all the actors involved in the motion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More investigations into these fundamental aspects will be necessary to optimize the fabrication and performance of these devices, but also reduce their side effects. Future research should focus more on the fundamental interactions with biological matrices (Palagi et al, 2017; Walker et al, 2015; Z. Wu et al, 2018) and also in the interaction between several of these nanomotors, which would also offer an interesting system to study in active matter physics (Hortelao, Simó, et al, 2020; Illien et al, 2017). The effects elements like ionic species or pH on the motion efficiency still need to be further investigated, as seemingly contradictory results arise (Arqué et al, 2020; De Corato et al, 2020; Tang et al, 2020), hinting at a much more complex interaction between all the actors involved in the motion.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced diffusion of urease‐powered nanomotors can improve the efficiency of anticancer drugs in 2D and 3D cultures of bladder cancer cells by showing an increased internalization when the nanomotors are targeted to a transmembrane protein (Figure 3a) (Hortelao et al, 2019; Hortelão et al, 2018). The same system was recently used in combination with the isotopes Iodine‐124 and Fluorine‐18 to study their suitability for in vitro and in vivo imaging via positron emission tomography (PET) coupled with computed tomography (PET‐CT) (Hortelao, Simó, et al, 2020), following a previous study that showed the successful imaging of motors of micrometer scale by chemisorption of Iodine into their gold surface (Vilela et al, 2018). Upon addition of urease, the nanomotors presented complex swarming behavior that could be tracked by PET‐CT (Figure 3b) and were homogeneously distributed in the bladder cavity of mice after intravesical administration (Figure 3c) (Hortelao, Simó, et al, 2020).…”
Section: Hybrid Machines At the Nanoscalementioning
confidence: 99%
See 2 more Smart Citations
“…Mimicking living cells and given the availability of chemical energy in the environment, artificial colloidal particles can be designed to self-propel through surface chemical reactions [1,2]. Besides serving as a model system to explore collective nonequilibrium phenomena [3], several technological applications have been envisaged for these active particles: from biomedical [4][5][6] to environmental remediation [7]. To achieve self-propulsion, different mechanism have been proposed such as diffusiophoresis [8], thermophoresis [9,10], momentum exchange [11], release of ions [12], and liquid-liquid phase separation [13].…”
mentioning
confidence: 99%